ANALISIS PENGARUH PENGETAHUAN, KETERAMPILAN DAN KEMAMPUAN TERHADAP KINERJA HOTEL PANORAMA UBUD - Tettie Setiyarti; Ni Putu Tirtayasih; Ida Bagus Radendra Suastama (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2020)
A professional hotel employee is required to have the knowledge, skills, and abilities that are qualified in their fields, so as to be able to produce maximum results according to the operational standards set by the hotel management. However, the facts on the ground show that employees' knowledge, skills, and abilities are still far from expectations. In this paper, the author tries to analyze the inuence of knowledge, skills, and abilities on employee performance at the Panorama Hotel Ubud, located in Gianyar Regency, Bali. This paper will discuss descriptively various variables related to employees' knowledge, skills and abilities, and their effects on their performance while working at the hotel. Data collection methods are done through observations, interviews, and documentations, while the analysis technique used is the classic assumption test, multiple linear regression and hypothesis testing. The results of this study indicate that employees' knowledge, skills, and abilities have a positive and significant effect on the level of performance of employees working in the Panorama Ubud Hotel.